(3OQGSI ebGQfIs - (3LdGd LhjOI YHOg(B, (3GdbUGUs ((3GdEScfOQjI(B:s (3eDSSI THGH GdLGeYI,s, 2006)
(3jVe edGeM hgjcd GdShb GdQCSeGdj hGdESdGej cEWGQ dJMOjO GdKef, GdedGeM GdQFjSjI dCOGA GdShb GdQCSeGdj, gjcd hedGeM GdShb GdESdGej, VhGHW GdCOGA aj GdShb GdESdGej, fXGe GdJSYjQ aj GdESdGe hCKQg Ydi GdfTGW GdEbJUGOjs
(3HHdjhZQGajG(B: (3U(B.399 (3GdedGMb U(B.394s
Keywords: (3GdCShGbs; (3GdEFJeGfs; (3GdEbJUGO GdESdGejs